(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this research was to explore the usefulness of soft skills for better English in employment opportunities for teachers. English is the preferred common language because it is an exact language. It allows a person to say what he or she wants to say without having to argue about the meaning. The research will use the secondary data approach. The result of the study shows that teaching as a multilayered presentation that demands a broad extent of skills and awareness including personal and interpersonal skills for successful achievement of handling classroom burden. Thus, the gift of teaching simply doesn’t entail a diffusion of knowledge from professor to people.